INTEGRATION OF STUDENT HABITUATION AND HEROIC EXEMPLARY STORIES IN CHARACTER BUILDING AT MIN 2 DAIRI - Syaripudin, Ahmad; Noor Auliya Huda,; Zarkasih Putro, Khamim; Sahanum Bintang, Rahma (AULADUNA: Jurnal Pendidikan Dasar Islam, 2025)
This study explores the role of civic education, heroic stories, and habituation activities in building a generation with character in Madrasah Ibtidaiyah. This study uses a descriptive qualitative approach, which focuses on an in-depth understanding of how the three components are applied in the context of education in madrasahs. Data were collected through interviews with educators, direct observation of learning activities, and documentation studies related to implementing civic education and heroic stories. The results of the study indicate that civic education in Madrasah Ibtidaiyah plays an important role in shaping moral and ethical values, while heroic stories provide inspiration about sacrifice and courage that strengthen students' nationalism. In addition, habituation activities such as disciplined behaviour, nationalism, and social responsibility also contribute significantly to character formation. This study suggests the importance of integrating the three aspects in the curriculum and educational practices to produce a generation that is not only academically intelligent but also has integrity and strong character.